A Histological Comparison of a New Pulp Capping Material and Mineral Trioxide Aggregate in Rat Molars - Moazzami, Fariborz; Ghahramani, Yasmin; Tamaddon, Ali Mohammad; Dehghani Nazhavani, Ali; Adl, Alireza (Iranian Endodontic Journal, 2013)
Introduction: Recent investigations have attempted to improve regenerative endodontics with the help of stem cell therapy. In vitro studies have shown the ability of different agents to stimulate the differentiation of dental pulp stem cells (DPSC) into odontoblast-like cells. A combination of dexamethasone, β-glycerophosphate and Vitamin D has been proven to induce a successful differentiation. The aim of this animal study was to evaluate the effect of this combination, named odontoblastic differentiating material (ODM), on pulp tissue when used as a capping material. Materials and Methods: Sixty maxillary right and left molars of 30 Sprague-dawley rats were selected for this study. The teeth were exposed under sterile condition. Half of the teeth were capped with mineral trioxide aggregate (MTA) and the other half with ODM. All cavities were restored with glass ionomer. The rats were sacrificed at post-operative intervals of 2 weeks and 2 months. Samples were histologically evaluated for the degree of inflammation and reparative dentin formation. Finally the data was analyzed with Mann-Whitney and Chi-Square tests. Results: Reparative dentin formed in all groups within both time periods and there was no statistically significant difference between the groups in the mentioned time periods. The MTA group, however, showed a statistically significant reduction in inflammation at both time intervals (P<0.05). Compared to MTA, ODM samples showed a greater amount of inflammation in the pulp tissue. Conclusion: ODM, as a pulp capping material, can induce dentinal bridge formation.